Methodological proposal for an optimal management of Social-Ecological Systems in relation to large-scale mining in Peru - Dueñas Militza; Ferrer Jorge (E3S Web of Conferences)
Significant participation of mining activities in the economic indicators of countries and extraction of raw materials to produce goods is relevant to evaluate management of the social-ecological systems in which they operate. This article proposes a methodology that integrates design principles (resource use rules), resilience principles (adaptive strategies that respond to disturbances) and principles linked to good practices promoted in the sector. Under this proposal, it is considered that design principles and resilience principles guide management of organizations and constitute pillars that strengthen organizational capabilities, the latter being the essence for optimal management of SES. Peru is characterized by its leading position in world ranking in mining production and reserves. Through the proposed methodology, this article studies mining companies considering value of mining production, mineral diversification and participation of companies in the mineral production, resulting that the optimal management of SES, in relation to large-scale mining, is “in development”, with partial compliance.